TINJAUAN HUKUM INTERNASIONAL MENGENAI SERANGAN UDARA DI BANDAR UDARA INTERNASIONAL BAGDAD JANUARI 2020 - Afandi, Muhajir; Jayakusuma, Zulfikar; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the most important purpose of the United Nations establishment isto maintaining the international peace and security through the prohibition on theuse of force among states to settle their problem which has been enshrined underUnited Nations Charter (UN Charter). One of the exceptions for states to use theirforce is in the situation of self-defense against the prior attack directed againstvictim state under Article 51 of the UN Charter. Despite the prohibition provisionunder UN Charter, there are still violations to this provision by states, veryrecently was the attack directed against Baghdad International Airport in Iraq byUnited States on the basis of self-defense however the condition defined in theArticle 51 of UN Charter was not fulfilled hence it made United StatesConduction Estabilshed the nature of violation to the Article 2(4) of UN Charter.The type of research carried out through normative-juridical researchwhere this research is conducted on the basis of legal principles which startedfrom certain written authorities as well as priorly identifying the provisions thathas been enshrined in certain law. In this study, the data sources used weresecondary data with primary, secondary and tertiary legal materials cerried outby the library research means.The results obtained through the research proves that, firstly, that theUnited States attack against Baghdad International Airport of Iraq constitutes aviolation to the non use of force obligation, constitutes an act of Agressionfurthermore the violation of good faith principle towards UN Charter and theAgreement Between the United States of America and the Republic of Iraq.Secondly, the ‘Self-Defense’ Basis by United States Government could not bedeem lawful as the condition under Article 51 nor the condition under ‘CarolineTest’ was never fulfilled.Keywords : UN Charter – Use of Force – Pacta Sunt Servanda – Self-defenseby States